Parents biologiques et parents adoptifs d’enfants ayant une déficience intellectuelle: Birth parents and adoptive parents of children with developmental disabilities - Beaudoin, France (Revue francophone de la déficience intellectuelle, 1991)
L’adoption des enfants ayant une déficience intellectuelle est un phénomène relativement nouveau et très peu exploré. L’étude présentée fait le point sur les données accessibles sur ce type d’adoption depuis trente ans, au Québec comme dans d’autres pays. La dynamique des parents d’enfants ayant une déficience intellectuelle est par la suite analysée. Le vécu des parents biologiques et leur processus d’adaptation à la déficience de l’enfant est repris en détails puis comparé au vécu des parents adoptifs. Enfin, les variables favorisant l’adaptation des parents à leur enfant déficient intellectuel sont décrites, que ces parents soient biologiques ou adoptifs. Abstract The adoption of children with intellectual disabilities is a relatively new and little explored phenomenon. This study reviews the data available on this type of adoption over the past thirty years, in Quebec as well as in other countries. The dynamics of parents of children with intellectual disabilities are then analyzed. The experiences of the biological parents and their process of adaptation to the child's disability are reviewed in detail and compared to the experiences of the adoptive parents. Finally, the variables that promote parents' adaptation to their child with an intellectual disability are described, whether these parents are biological or adoptive.